Law in the Roman provinces - Czajkowski, Kimberley; Eckhardt, Benedikt; Strothmann, Meret; Czajkowski, Kimberley; Eckhardt, Benedikt; Strothmann, Meret (Oxford University Press, 2020)
The study of the Roman empire has changed dramatically in the last century, with growing emphasis on local experiences rather than a sole focus on imperial elites. This volume explores how law fits into this new, decentralized picture, utilizing a series of case studies to explore variations in the operation of law between different regions.
This edition also issued in print: 2020. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on June 29, 2020)
Keywords: Römisches Recht; Provinz; Römisches Reich